UMP to manage Community College smart partnership collaboration programme - UMP, PNC
Universiti Malaysia Pahang (UMP) became the first university appointed by Higher Education Ministry’s Department of Community College Studies (JPKK) to manage a smart partnership programme involving community colleges and automotive companies in a move to produce skilled workers who would contribute to the development of the country’s economy in automotive.